Cocaine Intoxication and Thyroid Storm - Mary E. Lacy MD; Kristina M. Utzschneider MD (SAGE Publishing, 2014)
Introduction . Cocaine, a widely used sympathomimetic drug, causes thermoregulatory and cardiac manifestations that can mimic a life-threatening thyroid storm. Case . A man presented to the emergency department requesting only cocaine detoxification. He reported symptoms over the last few years including weight loss and diarrhea, which he attributed to ongoing cocaine use. On presentation he had an elevated temperature of 39.4°C and a heart rate up to 130 beats per minute. Examination revealed the presence of an enlarged, nontender goiter with bilateral continuous bruits. He was found to have thyrotoxicosis by labs and was treated for thyroid storm and cocaine intoxication concurrently. The patient was ultimately diagnosed with Graves' disease and treated with iodine-131 therapy. Conclusion . Cocaine use should be considered a possible trigger for thyroid storm. Recognition of thyroid storm is critical because of the necessity for targeted therapy and the significant mortality associated with the condition if left untreated.